The Sociolinguistic Consumption of K-pop - Samosir, Nora; Wee, Lionel (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The notion of sociolinguistic consumption distinguishes between the direct consumption of languages as denotational codes and the indirect consumption of linguistic repertoires that result from engaging in various activities. Since consumption as identity construction means gaining membership into a community of like-minded others, this raises the question of what the presence of these others might mean for the indirect consumption of linguistic repertoires as well as whether initial interest in one activity might lead to interest in yet other activities in a kind of chain consumption, thus further expanding the linguistic repertoire. This paper shows that K-pop presents us with just such scenarios. It makes the following three points. One, experienced consumers of K-pop provide translations and glossaries of key terms for newer K-pop fans, serving as language brokers. Two, interest in K-pop can lead to interest in other aspects of Korean culture, indicating the need to recognize that consumption can foster an anthropological stance. Finally, the indirect consumption of linguistic repertoires can, in turn, lead to the direct consumption of denotational codes, with implications for the roles of identity and investment in language learning.